Answer:
m is -2 and c is -1
Step-by-step explanation:
• Let's first phrase out the general equation of a line
[tex]{ \rm{y = mx + c}}[/tex]
[ remember that a general line equation must be in slope - intercept form as shown above ]
• from our question, we are given the equation;
[tex]{ \rm{3y + 6x = - 3}}[/tex]
• let's make y the subject in order to make the equation in slope - intercept format.
→ remember to apply "subject making knowledge"
[tex]{ \rm{3y = - 3 - 6x}} \\ \\ { \rm{3y = - 6x - 3}} \\ \\ { \rm{ \frac{3y}{3} = \frac{ - 6x}{3} - \frac{3}{3} }} \\ \\ { \boxed{ \rm{y = - 2x - 1}}}[/tex]
• The above boxed equation is now a general equation. Let's extract out slope, m and y-intercept, c
[tex]{ \rm{m \: \dashrightarrow \: - 2}} \\ \\ { \rm{c \: \dashrightarrow \: - 1}}[/tex]